Pengaruh Harga Jual, Persediaan Bahan Jadi, Strategi Pemasaran Terhadap Omset Penjualan Di UMKM Surabaya - Afrinia Dewi Kusmiarni; Chikita Swarna Putri Rahmadhan; Nindya Kartika Kusmayati (Pusat Riset dan Inovasi Nasional, 2025)
This study examines the impact of selling price, finished goods inventory management, and marketing strategy on sales turnover at Ayam Bakar Pak D Restaurant, Nginden Surabaya. Using quantitative methods and multiple linear regression analysis, the findings reveal that all three variables collectively influence sales turnover (F-value = 10.317, p = 0.000). However, partial analysis indicates only selling price (X1) has a significant positive effect (t = 4.591, p = 0.000), while finished goods inventory (X2)and marketing strategy (X3) show no significant impact. The regression equation derived is Y = 4.701 + 0.415X1 - 0.007X2 - 0.140X3 + e, emphasizing pricing strategy as a key driver of sales performance.